2019
DOI: 10.33678/cor.2019.005
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial bridge characteristics and coronary atherosclerotic markers

Abstract: Klinický význam svalového můstku (myocardial bridge, MB) pro celý systém věnčitých tepen a koronární aterosklerózu je stále předmětem diskuse. Cílem této studie bylo zjistit možnou spojitost mezi charakteristikami MB (délka, hloubka, přítomnost a místo proximální stenózy) a markery koronární aterosklerózy (kalcifi kace koronárních tepen [coronary artery calcifi cation, CAC], pláty, stenózy a objem perikardiálního tuku [pericardial fat volume, PFV]). Pacienti a metody: Z celkového počtu 225 po sobě následujícíc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Apart from the MB length and LAD coronary stenotic severity, no other risk factors were found to significantly affect abnormal FFRCT values in our study. Other studies have found that MB depth was also related to myocardial ischemia (Nafakhi et al, 2019) and that longer or deeper MB did not cause severe dynamic compression on the coronary artery and subsequently abnormal FFRCT values (Halliburton et al, 2011). Our study has analyzed patients with MB and patients with MB accompanied by atherosclerosis, whereas other authors only included LAD MB patients without any other abnormalities or without performing stratified analysis (Rubinshtein et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Apart from the MB length and LAD coronary stenotic severity, no other risk factors were found to significantly affect abnormal FFRCT values in our study. Other studies have found that MB depth was also related to myocardial ischemia (Nafakhi et al, 2019) and that longer or deeper MB did not cause severe dynamic compression on the coronary artery and subsequently abnormal FFRCT values (Halliburton et al, 2011). Our study has analyzed patients with MB and patients with MB accompanied by atherosclerosis, whereas other authors only included LAD MB patients without any other abnormalities or without performing stratified analysis (Rubinshtein et al, 2013).…”
Section: Discussionmentioning
confidence: 97%